Has Digitalization Boosted the Rural Tourism Income?—Evidence from Prefecture-Level City Panel Data in China - Qirui Zhang; Hao Feng; Xinhui Feng; Wangfang Xu; Longbao Wei (Land)
The agricultural industry is a vital driver of rural economic development and a primary income source for farmers. Rural tourism, which relies on rural resources, is a key component of the agricultural industry. With the rapid development of agricultural digitalization, the income of the rural tourism industry has been significantly influenced. This article categorizes rural tourism landscapes into cultural and natural types based on regional resources. It examines the impact of digitalization on rural tourism income using the generalized least squares method with panel models and explores the mechanisms of digitalization’s influence through a moderation effect model. Analysis indicates that digitalization positively impacts rural tourism with noticeable regional heterogeneity. There is also a significant positive moderating effect of synergistic cultural and natural factors. Natural factors positively affect rural tourism, with digitalization having the most pronounced positive moderating effect on income from natural landscapes. This article suggests that decision-makers should promote digital development to boost rural tourism revenue, tailoring digitalization efforts to regional conditions and focusing on the unique characteristics of natural and cultural landscapes to effectively enhance the rural tourism industry.